Quality Of Health Services For Bpjs Patients At Waled Hospital, Cirebon Regency - Mulya Apriliani; Sabrina Nur Febrianti; Hery Nariyah; Moh. Sutarjo (Journal of Social Research, 2024)
This study aims to determine the quality of health services for patients of the Social Security Administering Agency (BPJS) at the Waled Regional General Hospital (RSUD), Cirebon Regency. A qualitative approach was used in this research, with a purpose sampling method to provide an overview of the phenomena that occurred. Service Quality based on the theory of Parasuraman, Zeithaml and Berry (1990) in Muninjaya (2011) contains five dimensions, namely reliability, responsiveness, assurance, empathy and physical evidence. The findings showed that it was not comfortable because there were several complaints regarding the cleanliness of the toilets, where some bathrooms had a slight smell and slippery floors. Second, the high number of patients registering causes long waiting times, indicating an inefficient registration process and having a negative impact on patient conditions. Third, the behavior of health workers who are less friendly and communicative reduces patient trust and comfort, emphasizing the importance of a professional and empathetic attitude. Fourth, the problem of collecting laboratory results yourself without going through a medical officer can cause delays in obtaining important medical information. Fifth, the queues at the drug collection counters cause many patients to have to buy medicines outside the Waled Regional Hospital pharmacy. Lastly, the lack of cleaning facilities and cleaning staff worsens hospital environmental conditions, lowering the standard of health services. These problems demand serious attention to improving the quality of health services that focus on cleanliness, efficiency, and better interaction between staff and patients.